"I feel happier in myself with the dogs": the perceived impact of a prison animal programme for well-being. Issue 2 (10th February 2022) - Mercer, Jenny; Williams Davies, Ella; Cook, Megan; Bowes, Nic J.
Abstract : Purpose: Amid concerns regarding prisoner well-being, growing evidence indicates that prison animal programmes (PAPs), most commonly involving dogs, have significant therapeutic potential. Published research on this topic from the UK remains sparse, and more is needed to determine the type of programmes which work best and for whom. This study aims to explore the perceived benefits of a short-term PAP on the well-being of a sample of individuals assessed as at risk of self-harm. Design/methodology/approach: Participants with complex mental health needs in a category B prison took part in a four-week programme where two dogs were brought in for interactions once a week. Semi-structured interviews were conducted with eight participants at the end of the programme. Findings: Three themes were identified through thematic analysis: "A Safe Space for Emotional Experience", "An Opportunity to Connect" and "Being Human". The narratives offered a range of perceived benefits which illustrated the potential of dog based PAPs for enhancing well-being and consistency with desistance goals. Practical implications: The findings illustrate that even short-term interactions with dogs can be impactful and provide evidence for other practitioners about how this approach may be used with individuals with complex mental health needs. Originality/value: The study highlights the therapeutic potential of the presence of animals in prisons. The research contributes to the limited literature about PAPS in the UK.